DESAIN ALAT DETEKSI WAJAH DAN SUHU TUBUH BERBASIS SENSOR INFRARED UNTUK APLIKASI SPRAY HAND SANITIZER OTOMATIS - Ilmiatul Masfufiah; Kharis Yulianto Setyo Adi N. S; Wahyu Setyo Pambudi (Prosiding Seminar Nasional Sains dan Teknologi Terapan, 2022)
The spread of the Covid-19 Virus is increasing in Indonesia. The society encouraged to have a healthy lifestyle. One of the ways is using hand sanitizer which is useful to kill the virus. Today, hand sanitizer currently uses a manual system or spray bottle. It can spread the virus by spray bottle contact There is a method to detect the Covid-19 virus by human body temperature. The aim of this research was to design an automatic hand sanitizer spray system without touching bottle spray with an infrared base and Haar Cascade Classifier method. The Haar Cascade Classifier method was chosen because the data processing was too fast and suitable for real-time video capture. The results of hand sanitizer tool test could detect the face as a trigger for the release of hand sanitizer as well as detect body temperature. Hand sanitizer system used thermogun as a comparison. It was obtained 14.28% before the calibration process for error percentage and calibration was obtained at 2.87% for error percentage process.Makin an automatic hand sanitizer spray that used face detection and body temperature with infrared base needed several components, such as MLX90614 as a temperature sensor, a webcam camera as an optic for detecting faces, a laptop for Arduino serial communication with a webcam, Arduino Uno as a microcontroller, buzzer as an alarm indicator high temperature, 2 servo motors to pull the hand sanitizer lever and a 16x2 alphanumeric LCD to display body temperature. In face detection, this research used Haar Cascade Classifier method. The success rate of the tool reached 84.6%.